Considering pollution in the higher education (HE) service ecosystem: The role of students' evaluation surveys. Issue 6 (9th October 2017) - Díaz-Méndez, Montserrat; Saren, Michael; Gummesson, Evert
Abstract : Purpose: From a service ecosystem perspective, the purpose of this paper is to examine students' evaluation surveys as a tool used by most higher education (HE) institutions worldwide to measure teaching quality with consequences for tenure and promotion. Design/methodology/approach: This study is based on the service-dominant (S-D) logic and specifically on the service ecosystem approach. Through an in-depth literature review and analysis the authors explore the effect of student evaluation surveys on the value co-creation process, describe the role they play in the HE ecosystem and critically evaluate their efficacy. The research is based on empirical data from the literature and previous studies findings. Findings: The literature review highlights the detrimental consequences of the use of students' evaluation surveys for teachers and students and for the rest of actors of this service. The authors argue that institutions should embrace a service ecosystem perspective based on S-D logic. The authors highlight the role of institutions as moderators of the interactions between actors and, finally, the authors have introduced the concept of "service ecosystem pollution" which the authors define as the presence or introduction of disruptive elements in the service ecosystem adversely affecting the nature of value co-creation. Practical implications: This study emphasizes the importance for HE institutions to embrace a service ecosystem approach so as to foster and preserve the value co-creation processes taking place within the interactions among the HE actors. Conclusions drawn from this paper suggest that HE institutions should focus on strategies such as investing in improving students' and teachers' operant resources rather than polluting the HE service ecosystem with the use of students' evaluation surveys. Originality/value: Hitherto there are no studies analyzing the tools HE institutions use to measure teaching quality from a service ecosystem perspective. The study is especially valuable due to the consequences and the use of these measures entails for teachers, students and society.